Adult responses to child negotiations: effect of gender and advocacy - Choo, Germaine Jing Wen (Nanyang Technological University, 2023)
Literature on gender gaps in negotiations have found that women tend to ask for less and are given less. Additionally, women who advocated for themselves compared to advocating for others’ benefit faced more social backlash. Only one prior study has explored gender gaps in negotiations in children, but it is unknown as to how these develop. The current study explores whether adults respond differently to children in negotiations depending on child gender and advocacy style, as this may contribute to the development of gender gaps in negotiations. 284 US participants recruited via Prolific.co were shown hypothetical scenarios where a Scout completed a chore (e.g., sorting recycling) in exchange for a $5 donation to charity. After each scenario, participants were prompted to offer an additional donation and give a performance rating. After all scenarios, participants evaluated the Scouts based on seven positive and seven negative traits. A between-subject 2 (girl, boy) x 2 (self-, other-advocating) x 2 (child-, system-prompted) design was used. Prompt condition was varied to determine if responses would differ if children were shown negotiating by themselves versus if a computer-generated prompt was used. Results found that participants gave more positive trait evaluations to other-advocating girls than boys, suggesting that other-advocating girls may receive less social backlash, similar to other-advocating women in negotiations. There were no other significant differences in how adults responded, suggesting that adults may not reward children differently according to gender or advocacy. This study is the first to explore a possible origin of gender gaps in negotiations, however further studies are required.